2022
DOI: 10.1039/d1lc01055g
|View full text |Cite
|
Sign up to set email alerts
|

Direct MYD88L265P gene detection for diffuse large B-cell lymphoma (DLBCL) via a miniaturised CRISPR/dCas9-based sensing chip

Abstract: Traditional methods for single-nucleotide variants based on the amplification and the fluorescent signals require expensive reagents and cumbersome instruments, and they are time-consuming for each trial. Here, a porous anodised...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The ionic current increased with the concentration of mutated genes, establishing a limit of detection of 1.37 nM and a sensitivity of 0.02 μA ng −1 . 184 A non-enzymatic uric acid (UA) sensor was developed by Su et al based on a 2-thiouracil (2-TU)-modified NAA membrane. The intrinsic rectification property of the NAA membrane was characterized by an ICR ratio of 7.2.…”
Section: Applications Of Naa As An Iontronic Platformmentioning
confidence: 99%
“…The ionic current increased with the concentration of mutated genes, establishing a limit of detection of 1.37 nM and a sensitivity of 0.02 μA ng −1 . 184 A non-enzymatic uric acid (UA) sensor was developed by Su et al based on a 2-thiouracil (2-TU)-modified NAA membrane. The intrinsic rectification property of the NAA membrane was characterized by an ICR ratio of 7.2.…”
Section: Applications Of Naa As An Iontronic Platformmentioning
confidence: 99%
“…Methicillin-resistant Staphylococcus aureus (MRSA) can be detected through fluorescence in situ hybridization (FISH) by connecting a magnetic bead to the dCas9 protein (Guk et al, 2017 ). In addition, a diagnostic method for detecting the change in the ionic current rectification caused by the binding of dCas9/sgRNA to a target in an aluminum-based sensing chip has been reported (Sun et al, 2022 ).…”
Section: Nucleic Acid Diagnosticsmentioning
confidence: 99%
“…31 Currently, the detection signal outputs in many CRISPR/dCas9 detection systems mainly rely on fluorescence and electrochemistry. 29,32,33 The detection of lowconcentration DNA is still a challenge. New signal output platforms that can improve detection sensitivity are worth exploring to integrate with dCas9 techniques, which can further widen the applications of the CRISPR/dCas9 detection systems.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Target recognition requires a protospacer adjacent motif (PAM) sequence, and the dCas9 protein is a functional protein that can capture target DNAs in complex systems via identifying the PAM sequences . Due to the flexibility of sgRNA design, the CRISPR/dCas9 system is flexible in the DNA detection in various systems, e.g., bacteria, cancer, viral, and genetic mutations. It has been reported that dCas9 protein is effective in distinguishing single-nucleotide polymorphisms (SNPs) . Currently, the detection signal outputs in many CRISPR/dCas9 detection systems mainly rely on fluorescence and electrochemistry. ,, The detection of low-concentration DNA is still a challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation